Road traffic noise affects annoyance during urban built and forest walks, but not repetitive negative thinking or connectedness with non-human nature: A randomized controlled trial - Julia Schaupp; Jean-Marc Wunderli; Beat Schäffer; Karin Hediger; Nicole Bauer (PLoS ONE, 2026)
Previous research has examined the potential of exposure to greenspaces to reduce maladaptive emotion regulation strategies, such as repetitive negative thinking, and to foster connectedness with non-human nature. However, research comparing green and urban built environments often primarily attributes the benefits of greenspace exposure to their positive features, without explicitly addressing road traffic noise as a potential stressor in urban settings. This study investigated how 30-minute walks in forests and urban built environments with varying levels of road traffic noise in Zürich, Switzerland, affect noise annoyance, connectedness with non-human nature and repetitive negative thinking. By accounting for traffic noise, the aim was to isolate the effects of environment (urban built. vs. forest) with minimal confounding. Data from 354 healthy adults were analyzed. Road traffic noise annoyance was generally lower (i) in forests than urban built settings, (ii) in lower road traffic noise than higher road traffic noise settings, and (iii) in areas with longer than in those with shorter relative quiet time. Notably, the robust association between road traffic noise and annoyance was particularly pronounced in forests. In contrast, neither walking in forests nor in environments with lower road traffic noise nor such with longer relative quiet time was associated with a greater reduction in repetitive negative thinking, a stronger increase in nature relatedness or love and care for nature. The results underscore the role of road traffic noise as a significant health-related stressor and support the need for targeted noise mitigation—particularly around urban forests— to preserve their restorative potential. Additionally, the results highlight the relevance of quiet intervals and temporal noise patterns in shaping perceived annoyance, extending beyond average noise measurements. This study has been registered in the ISRCTN registry (ISRCTN48943261). https://www.isrctn.com/ISRCTN48943261 Registered 23.11.2023.